1990
DOI: 10.1007/bf00318663
|View full text |Cite
|
Sign up to set email alerts
|

Morphological effects of somatostatin on rat somatotrophs previously activated by growth hormone-releasing factor

Abstract: Correlative morphological and physiological analysis was carried out in order to clarify the role of somatostatin in the inhibition of the secretion of growth hormone (GH) from somatotrophs of the rat anterior pituitary gland in vivo. Transmission electron microscopy combined with immunogold labelling showed an increased number of exocytotic GH-containing secretory granules in somatotrophs fixed between 2 and 10 min after injection of GH-releasing factor (GRF). Injection of GRF also induced the appearance of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The relationship between morphological heterogeneity and functional heterogeneity of GH cells remains to be clarified. In the rat GH cells no obvious relationship was detected between the degreee of response to GH-releasing hormone and the different type of GH cells [Shimada et al, 1990].…”
Section: Discussionmentioning
confidence: 93%
“…The relationship between morphological heterogeneity and functional heterogeneity of GH cells remains to be clarified. In the rat GH cells no obvious relationship was detected between the degreee of response to GH-releasing hormone and the different type of GH cells [Shimada et al, 1990].…”
Section: Discussionmentioning
confidence: 93%
“…By contrast, only a few studies have investigated morphological features of somatotropes during inhibition or stimulation of GH secretion [20,21]. Shimada et al [21] suggest that inhibition of GH release by SRIH involves a change in distribution of microfilaments rather than microtubules. These authors found microfilament bundles running parallel to the plasmalemma in the space between granules at 2 and 5 min after injection of SRIH.…”
Section: Discussionmentioning
confidence: 99%
“…A number of physiological and biochemical studies in vivo and in vitro have been performed to examine the role of both somatostatins on the mechanism of GH secretion [4,15,18,19]. By contrast, only a few studies have investigated morphological features of somatotropes during inhibition or stimulation of GH secretion [20,21]. Shimada et al [21] suggest that inhibition of GH release by SRIH involves a change in distribution of microfilaments rather than microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Although it remains to be determined whether SRIF regulates pituitary Ca 2C levels independently of K C channels, GH release correlates with both frequency and amplitude of calcium oscillations, while calcium channel blockers and SRIF acutely suppress Ca 2C extrusion (Holl et al 1988). SRIF treatment resulted in Ca 2C -dependent redistribution of cytoplasmic microfilaments, without affecting intracellular somatotroph GH content (Shimada et al 1990), in addition to reduced association of exocytosis-associated RAB3B and SNARE proteins (Matsuno et al 2003 Adenylate cyclase/cAMP/PKA signalling SRIF inhibits pituitary adenylate cyclase/cAMP/PKA signaling, thereby inhibiting pituitary hormone synthesis and cell growth. SRIF inhibits cAMP production and ACTH secretion induced by CRH, forskolin, isoproterenol, vasoactive intestinal polypeptide (VIP), and cholera toxin in AtT-20 cells (Heisler et al 1982).…”
Section: Cmentioning
confidence: 99%